2020
DOI: 10.14573/altex.2003242
|View full text |Cite
|
Sign up to set email alerts
|

New approach methodologies (NAMs) for human-relevant biokinetics predictions

Abstract: Whereas much work has been devoted to the development of in vitro screening methods to capture biological effects (toxicodynamics) of chemicals, insight into the absorption, distribution, metabolism and excretion (i.e., ADME/biokinetics) of chemi- IntroductionThere are clear societal and scientific needs for the development and validation of predictive animal-free methods for safety evaluations to prevent adverse effects in humans caused by exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 113 publications
(172 reference statements)
0
28
0
1
Order By: Relevance
“…The results obtained do not apparently favor one of the two in vitro models and it can be concluded that both model systems can be equally well used to study human intestinal epithelial responses, thus selection may depend on the endpoint of interest. For instance, to derive uptake rates for pharmacokinetic modelling the robust and routinely used Transwell models might be the preferred approach 54 , while to emulate complex interactions in the intestine organ-on-chip models might be the preferred model [55][56][57] . It should be kept in mind that some specific gene functions are differently modulated in each model.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained do not apparently favor one of the two in vitro models and it can be concluded that both model systems can be equally well used to study human intestinal epithelial responses, thus selection may depend on the endpoint of interest. For instance, to derive uptake rates for pharmacokinetic modelling the robust and routinely used Transwell models might be the preferred approach 54 , while to emulate complex interactions in the intestine organ-on-chip models might be the preferred model [55][56][57] . It should be kept in mind that some specific gene functions are differently modulated in each model.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro methods can contribute to the refinement of the default UFs, while complying with the 3Rs principle of the reduction, refinement and replacement of animal testing (Russell and Burch 1959). Although the use of an interspecies differences UF may be eliminated when human cells and/or tissue are used in the transition towards an alternative risk assessment without animal experiments, it can still be useful to investigate these interspecies differences to gain confidence in the alternative method used and compare with an animal in vivo data (Punt et al 2020). To refine the UF for human variability, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The need to recreate this level of complexity, combined with a parallel drive to decrease dependence on animal experiments (for ethical, cost and reliability reasons), has led to intensive efforts in both academia and industry to generate more representative in vitro models of the PT. Recent indepth articles have reviewed this rapidly expanding field in detail [49,50], but the main areas of active research include more differentiated human-derived cell lines [51,52], reprogrammed stem cells [53], kidney organoids [54,55] and microfluidic devices (so-called kidney-on-a-chip) [56,57]. Each approach has advantages and disadvantages [49], for example organoids can partially mimic the threedimensional environment of the normal kidney, allowing the study of cross-talk between PT cells and surrounding interstitial cells in response to injury.…”
Section: New In Vitro Proximal Tubule Models To Screen For Drug Toxicitymentioning
confidence: 99%